Proactive inhibition deficits with normal perfusion after pediatric mild traumatic brain injury. Issue 18 (28th August 2019) - Mayer, Andrew R.; Stephenson, David D.; Wertz, Christopher J.; Dodd, Andrew B.; Shaff, Nicholas A.; Ling, Josef M.; Park, Grace; Oglesbee, Scott J.; Wasserott, Ben C.; Meier, Timothy B.; Witkiewitz, Katie; Campbell, Richard A.; et al.
Abstract: Although much attention has been generated in popular media regarding the deleterious effects of pediatric mild traumatic brain injury (pmTBI), a paucity of empirical evidence exists regarding the natural course of biological recovery. Fifty pmTBI patients (12–18 years old) were consecutively recruited from Emergency Departments and seen approximately 1 week and 4 months post‐injury in this prospective cohort study. Data from 53 sex‐ and age‐matched healthy controls (HC) were also collected. Functional magnetic resonance imaging was obtained during proactive response inhibition and at rest, in conjunction with independent measures of resting cerebral blood flow. High temporal resolution imaging enabled separate modeling of neural responses for preparation and execution of proactive response inhibition. A priori predictions of failed inhibitory responses (i.e., hyperactivation) were observed in motor circuitry (pmTBI>HC) and sensory areas sub‐acutely and at 4 months post‐injury. Paradoxically, pmTBI demonstrated hypoactivation (HC>pmTBI) during target processing, along with decreased activation within prefrontal cognitive control areas. Functional connectivity within motor circuitry at rest suggested that deficits were limited to engagement during the inhibitory task, whereas normal resting cerebral perfusion ruled out deficits in basal perfusion. In conclusion, current results suggest blood oxygen‐level dependent deficits during inhibitory control may exceed commonly held beliefs about physiological recovery following pmTBI, potentially lasting up to 4 months post‐injury.